Perspective of PPKN Stambuk 2022 Medan State University Students Regarding the 2024 Election Implementation System - Sinambela, Sulastri; Pinem, Octa Vioni; Panjaitan, Novia; Hutabarat, Lina; Halking, Halking (Education Achievement: Journal of Science and Research, 2024)
This research aims to examine and analyze directly the perspective of PPKN Stambuk 2022 students at Medan State University regarding the 2024 election implementation system. This mini-research proposal report will examine the perspective or level of understanding of PPKn Stambuk 2022 students regarding the election system. The aim of this mini research is to describe or illustrate the understanding of the 2022 PPKn Stambuk students at Medan State University regarding the 2024 election system in Indonesia. The research method used in this research is qualitative descriptive research. Data collection techniques through interviews, documentation and data sources taken from PPKn students to find out how the 2022 PPKN Stambuk Students at Medan State University understand the 2024 Election Implementation System. The results of the research show that students' understanding of the election system is concluded that the election system has a big role in optimization and voice his opinion according to his choice. The 2022 PPKn Stambuk students' opinions on the electoral system reflect the public's desire to participate actively in politics. The hope of PPKn Stambuk 2022 students is that the implementation of the election system can be better, starting from voter registration, counting to reporting results, which is carried out transparently.